1984
DOI: 10.1159/000215099
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Procoagulant Factors in Mononuclear Phagocytes

Abstract: Mononuclear phagocytes can be activated to develop enhanced expression of a wide range of macromolecules and mediators. Amongst these are several procoagulants, most notably thromboplastin. A variety of stimuli (particles, ligands for cell surface receptors, and some pharmacological agents) enhance procoagulant expression. We indicate that such enhancement may contribute to intra-and extravascular coagulation in several types of infections. We also point to the paucity of knowledge on the biosynthesis and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…chronic inflammatory diseases, delayed type hypersensitivity, rejec tion of organ transplants or cancer [reviewed in ref. 5], [3,17,18] including adherence [19]. This could be confirmed in our present study using hydrophobic Teflon as the cultivation sub strate.…”
Section: Discussionsupporting
confidence: 85%
“…chronic inflammatory diseases, delayed type hypersensitivity, rejec tion of organ transplants or cancer [reviewed in ref. 5], [3,17,18] including adherence [19]. This could be confirmed in our present study using hydrophobic Teflon as the cultivation sub strate.…”
Section: Discussionsupporting
confidence: 85%
“…Once associated with a vegetation monocytes can be induced to generate thromboplastin by bacteria, bacterial products, ly*phokines, or complement (28,29).Phagocytosis of bacteria on the vegetational surface could be a stimulus since phagocytosis of S. sanguis and ,S. epidermidis by human as well as rabbit monocytes (30) in vitro was shown to increase thromboplastic activity in these cells. Since infected vegeiations contain more monocytes than sterile vegetations do (3), the elevated procoagulant activity of infected vegetation could be due to activation of the monocytes, to a larger population of these cells, or most probably a combination of these two.…”
Section: Discussionmentioning
confidence: 99%
“…MPCA is generated by a number of foreign stimuli (e.g., bacterial lipopolysaccharide (LPS), lectins, allogeneic cells) and endogenous activators such as macrophage-procoagulant-inducing factor (MPIF), IFNy in combination with a second signal, complement components and immune complexes (Dean et al, 1984;Ryan and Geczy, 1987;Geczy and Jones, 1988). Fibach et al (1985) showed that some chemotherapeutic drugs induced procoagulant activity on the promyelocytic cell line HL60.…”
mentioning
confidence: 99%